“PENGARUH KECANDUAN BERMAIN GAME ONLINE DAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X DI SMAN 1 RANAH PESISIR - Apri Yuneza; Salman M. Noer; Reni Respita (Ekasakti Educational Scientific Journal, 2025)
The purpose of this study was to see the Influence of Online Game Addiction andLearning Facilities on Student Learning Outcomes in the Economics Subject of Class X atSMAN 1 Ranah Pesisir. This type of research is a quantitative approach. The population inthis study was 297 students of class X at SMAN 1 Ranah Pesisir. Sampling using theProportionate Random Sampling technique, the sample obtained was 75 students. The resultsof this study indicate that there is an influence of online game addiction ( ) and learningfacilities ( ) on student learning outcomes (Y) in the economics subject of class X at SMAN1 Ranah Pesisir. The significance value for the influence of ( ) and ( ) simultaneously onY is 0.001 <0.05 and the F-count value is 7.573> Ftable 3.124. This shows that there is aninfluence of online game addiction and learning facilities together on student learningoutcomes in the economics subject of class X at SMAN 1 Ranah Pesisir.